Stability augmentation system for semi active suspension system to study ride performance with magnetorheological damper - Muhammad Akmal Mohd Daruis, 1988-; Pakharuddin Mohd. Samin, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2011